1971
DOI: 10.1037/h0031513
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the structure of vocational interests.

Abstract: Compared the internal structural relationships of scales from the svib, the kuder occupational interest survey, holland's vocational preference inventory, the minnesota vocational interest inventory, and the american college testing program vocational interest profile. The configurations of the scales for all the inventories were found to be similar and to conform to the circular configurations of interest proposed by A. Roe and J. Holland. The common configuration of vocational interests was used to reconcile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
34
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 25 publications
9
34
0
Order By: Relevance
“…A recent metastructural analysis of Holland's measures supported the accuracy of Holland's RIASEC arrangement for U.S. White majority samples (Tracey & Rounds, 1993) but not for international samples and U.S. ethnic samples . Other major support comes from two classic studies (Cole, 1973;Cole & Hanson, 1971) that examined the relationships among scales based not only on Holland categories but also on a wide variety of occupational interests and basic structures. After applying a spatial analysis to these scales, Cole concluded that the patterns of the scales for men and women across the various inventories were similar and conformed to Holland's RIASEC circular structure.…”
Section: The Structure Of Basic Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent metastructural analysis of Holland's measures supported the accuracy of Holland's RIASEC arrangement for U.S. White majority samples (Tracey & Rounds, 1993) but not for international samples and U.S. ethnic samples . Other major support comes from two classic studies (Cole, 1973;Cole & Hanson, 1971) that examined the relationships among scales based not only on Holland categories but also on a wide variety of occupational interests and basic structures. After applying a spatial analysis to these scales, Cole concluded that the patterns of the scales for men and women across the various inventories were similar and conformed to Holland's RIASEC circular structure.…”
Section: The Structure Of Basic Interestsmentioning
confidence: 99%
“…A revision of Cole's (1973) and Cole and Hanson's (1971) studies seemed appropriate. For one thing, their analysis involved separate interest inventories designed for men and women, whereas today both sexes are scored on the same set of basic interest scales, allowing a more direct comparison.…”
Section: Another Look At Sex and Structurementioning
confidence: 99%
“…This theory accounts for six types of people -realistic, investigative, artistic, social, enterprising and conventional -and assumes there is a professional environment that corresponds to each. Holland's (1962 and1973) theory has gained much empirical support in the last two decades (Cole and Hanson (1971), Edwards and Whitney (1972), Mount and Mchinsky (1978), O'Neil (1977), Reuterfors, Schneider and Overton (1979), Salomone and Slaney (1978) and Spokane and Derby (1979)). According to Holland's theory, the accountant stereotype is a specific case of the conventional type that matches the secretarial administrative environment.…”
Section: Accountants' Personality Typesmentioning
confidence: 99%
“…The CDM authors were originally influenced by factor analytic research with White American participants (Campbell, 1974;Cole & Hanson, 1971;O'Shea & Harrington, 1972) that showed that the RIASEC model explained most of the variance being measured by inventories. At that time, only a few studies were found that compared the vocational interests of non-Whites with those of Whites.…”
mentioning
confidence: 99%